The status of Velvet Scoter Melanitta fusca breeding in Georgia - Paposhvili, Nika (Wildfowl, 2018)
The first ever survey of all seven potential breeding lakes for Velvet Scoter Melanitta fusca fusca in the Javakheti plateau region of southern Georgia found that nesting was confined to just one traditionally occupied site, at Lake Tabatskuri. Intensive observations revealed that c. 25–35 pairs were present at Lake Tabatskuri during mid- May to mid-June in 2017 and 2018, but substantially fewer pairs actually nested at the lake, and all that did so built nests on the only island in the lake. Hatching success (65% of eggs successfully hatched in 2017, 51% in 2018) was lower than in North American White-winged Scoter M. f. deglandi studies (67–92%) and fledging success was relatively poor (29% of hatched ducklings survived to fledging compared to 5–10% in North America and 30% in Finland), suggesting challenges to the longterm perpetuation of the population. More research is required to determine the direct causes of the scoters’ poor reproductive success. Information from a questionnaire survey of local residents and observations made during the study suggested that interactions with Armenian Gulls Larus armenicus nesting on the islands, disturbance and removal of eggs by humans, and drowning of ducklings in active or abandoned fishing nets all contributed to poor overall reproductive success. Conservation actions to ameliorate some of these factors have already been initiated, but further research, monitoring and conservation is needed to safeguard for future generations this tiny disjunct population at its last location in Georgia, potentially in the entire region.